Biopesticide Trunk Injection Into Apple Trees: A Proof of Concept for the Systemic Movement of Mint and Cinnamon Essential Oils - Werrie, Pierre-Yves; Burgeon, Clément; Le Goff, Guillaume Jean; Hance, Thierry; Fauconnier, Marie-Laure (Frontiers in Plant Science, 2021)
The use of conventional pesticides is debated because of their multiple potential adverse effects on non-target organisms, human health, pest resistance development and environmental contaminations. In this setting, this study focused on developing alternatives, such as trunk-injected essential oil (EO)-based biopesticides. We analysed the ecophysiology of apple trees (Malus domestica) following the injection of Cinnamomum cassia and Mentha spicata nanoemulsions in the tree’s vascular system. Targeted and untargeted volatile organic compounds (VOCs) analyses were performed on leaf-contained and leaf-emitted VOCs and analysed through dynamic headspace–gas chromatography–mass spectrometry (DHS-GC-MS) and thermal desorption unit (TDU)-GC-MS. Our results showed that carvone, as a major constituent of the M. spicata EO, was contained in the leaves (mean concentrations ranging from 3.39 to 19.7 ng gDW–1) and emitted at a constant rate of approximately 0.2 ng gDW–1 h–1. Trans-cinnamaldehyde, C. cassia’s major component, accumulated in the leaves (mean concentrations of 83.46 and 350.54 ng gDW–1) without being emitted. Furthermore, our results highlighted the increase in various VOCs following EO injection, both in terms of leaf-contained VOCs, such as methyl salicylate, and in terms of leaf-emitted VOCs, such as caryophyllene. Principal component analysis (PCA) highlighted differences in terms of VOC profiles. In addition, an analysis of similarity (ANOSIM) and permutational multivariate analysis of variance (PERMANOVA) revealed that the VOC profiles were significantly impacted by the treatment. Maximum yields of photosystem II (Fv/Fm) were within the range of 0.80–0.85, indicating that the trees remained healthy throughout the experiment. Our targeted analysis demonstrated the systemic translocation of EOs through the plant’s vascular system. The untargeted analysis, on the other hand, highlighted the potential systemic acquired resistance (SAR) induction by these EOs. Lastly, C. cassia and M. spicata EOs did not appear phytotoxic to the treated trees, as demonstrated through chlorophyll fluorescence measurements. Hence, this work can be seen as a proof of concept for the use of trunk-injected EOs given the systemic translocation, increased production and release of biogenic VOCs (BVOCs) and absence of phytotoxicity. Further works should focus on the ecological impact of such treatments in orchards, as well as apple quality and production yields.